Visitor’s satisfaction towards the facilities at Pudu Ulu Recreation Park, Cheras - Aziz, Noramirah (2018)
The satisfaction of visitors to the park depends highly on what the benefits they get from the facilities of the park. This study was conducted to assess the satisfaction level of visitors on facilities at Pudu Ulu Recreation Park, Cheras and factors influencing their satisfaction level. In this study, descriptive and regression analysis were used to achieve the objectives. Result show that, among all the facilities provided in the park, the location of gazebo was found to have the highest of satisfaction while the number of kiosks in the park was rated the lowest level of satisfaction. Factors influencing the level of satisfaction are race, specifically the race Indian and Malay.